Social Entrepreneurship Development to Achieve Sustainability Goals Using SSM Analysis - Benedicta Evienia Prabawanti; Rizal Syarief; Meika Syahbana Rusli; Dwi Purnomo (Management Analysis Journal, 2023)
Measuring performance in social entrepreneurship is an important thing that needs to be done. This is an effort to ensure prosperity and maintain the sustainability of social entrepreneurship. This research aims to analyze the performance of social entrepreneurship and build a conceptual model of the strategy for assessing the performance of social entrepreneurship in the Special Region of Yogyakarta. The SSM research method was used to develop a conceptual model to measure the performance of social entrepreneurship. The results of the study concluded that measuring the performance of social entrepreneurship can be measured using measurement tools or indicators that focus on sustainable development goals (SDGs). This study also found the need for the role of the government or policy owners as actors who have an essential role in developing social entrepreneurship performance measurement tools. This is necessary to distinguish the target of achieving success through social and commercial entrepreneurship.